The Most Productive Years of Average Astronomers. (2nd October 2017) - Abt, Helmut A.
Abstract: We learned previously that geniuses and outstanding scientists have peak productivities in their 30s but produce little late in life. This time we consider average astronomers who have completed their careers (25 American Astronomical Society members who died recently) and found that they peak in their mid 40s and did half of their life's important output after age 50.